Implementasi Pendidikan Anti Korupsi Pada Perguruan Tinggi - Robby Nurtresna; Dika Ratu Marfu'atun; Mabsuti Mabsuti (Mediation : Journal Of Law, 2022)
Corruption in Indonesia is huge and like a disease that is difficult to cure. If this situation is allowed to continue like this, it is almost certain that sooner or later corruption will destroy this country. Of course, the eradication of corruption is not only the responsibility of law enforcement or the government, but also the shared responsibility of the entire nation. Therefore, efforts to eradicate corruption must involve all relevant stakeholders, ie. government, private and public. Anti-corruption education students are essential to be given sufficient knowledge about corruption and its eradication and encourage anti-corruption values such as honesty, care, independence, discipline, responsibility, hard work, simplicity, courage. and justice. All parties, both local governments, university leaders and lecturers, especially lecturers of anti-corruption education courses must pay special attention to this, considering the importance of anti- corruption students as followers of the nation. So, the development of an anti-corruption personality among students, to develop their spirit and competence as a driver of changing the life of society and a nation free from the threat of corruption, is still far from expectations.